Epigenome-wide association studies identify DNA methylation associated with kidney function - Chu, Audrey Y.; Tin, Adrienne; Schlosser, Pascal; Ko, Yi-An; Qiu, Chengxiang; Yao, Chen; Joehanes, Roby; Grams, Morgan E.; Liang, Liming; Gluck, Caroline A.; Liu, Chunyu; Coresh, Josef; et al. (Nature communications, 2017)
Chronic kidney disease (CKD) is defined by reduced estimated glomerular filtration rate (eGFR). Previous genetic studies have implicated regulatory mechanisms contributing to CKD. Here we present epigenome-wide association studies of eGFR and CKD using whole-blood DNA methylation of 2264 ARIC Study and 2595 Framingham Heart Study participants to identify epigenetic signatures of kidney function. Of 19 CpG sites significantly associated ( P < 1e-07) with eGFR/CKD and replicated, five also associate with renal fibrosis in biopsies from CKD patients and show concordant DNA methylation changes in kidney cortex. Lead CpGs at PTPN6 / PHB2 , ANKRD11 , and TNRC18 map to active enhancers in kidney cortex. At PTPN6 / PHB2 cg19942083, methylation in kidney cortex associates with lower renal PTPN6 expression, higher eGFR, and less renal fibrosis. The regions containing the 243 eGFR-associated ( P < 1e-05) CpGs are significantly enriched for transcription factor binding sites of EBF1, EP300, and CEBPB ( P < 5e-6). Our findings highlight kidney function associated epigenetic variation. Genome-wide association studies of kidney function show enrichment of associated genetic variants in regulatory regions. Here, the authors perform epigenome-wide association studies of kidney function and disease, identifying 19 CpG sites significantly associated with these.